Tourist satisfaction at tourism destination of Aan village, Klungkung, Bali - Zulfan, Muhammad; Paramita, Ratri; Agustini, Ni Putu Oka (YAYASAN MITRA PERSADA NUSANTARA, 2024)
This research aims to determine tourist satisfaction when visiting Aan Tourism Village and to find out what factors influence tourist satisfaction. Data collection was carried out using a questionnaire instrument which was administered to 20 tourists who visited Aan village in November 2023. The results of the research showed that tourist satisfaction was dominated by the accessibility factor to the Aan tourist village destination which was easy to reach, then followed by the availability of internet access, and tourist engagement with local culture and people. Apart from that, tourist satisfaction is also determined by good service from the manager, the cleanliness and beauty of the tourist village, as well as the friendliness of the local population.